The Influence of Nigella sativa on the Increase of IFN-γ and Quality of Life in Lung Cancer Patients Undergoing Chemotherapy - Mahendra, Reza Aditya; Pratiwi, Suryanti Dwi; Sartono, Teguh Rahayu; Rakhma, Sastia; Setijowati, Nanik (Jurnal Respirasi, 2025)
Introduction: In vitro and animal model studies have shown that Nigella sativa reduces cancer cell proliferation and improves chemotherapy effectiveness. Cellular activation triggers the production of IFN-γ by natural killer (NK) cells. This study examined the effect of Nigella sativa supplementation on IFN-γ levels and quality of life in lung cancer patients before and after interferon therapy. Methods: This study used a non-equivalent control experimental design involving 21 lung cancer patients undergoing initial chemotherapy at Dr. Saiful Anwar General Hospital, Malang, in 2023. The patients were divided into two groups: one group received standard chemotherapy, and another group received a combination of chemotherapy and Nigella sativa supplementation at a dose of 2x500 mg for nine weeks. The effects of this intervention were assessed by measuring IFN-γ levels using an enzyme-linked immunosorbent assay (ELISA) kit and evaluating quality of life using the European Organization for Research and Treatment of Cancer (EORTC) Core Quality of Life (QLQ-C30) questionnaire before and after the fourth cycle of chemotherapy. Results: The results showed a significant increase in IFN-γ levels in the combination group undergoing chemotherapy and receiving Nigella sativa supplementation (6140.44±2233.89) compared to the standard chemotherapy group (3827.08±1722.79), with a p-value of 0.015. Quality of life improved in both groups, with scores of 53.70±6.05 before and 65.74±14.70 after chemotherapy (p=0.000). Conclusion: This study found that Nigella sativa supplementation can enhance IFN-γ levels and quality of life in lung cancer patients after four chemotherapy treatment cycles. These findings indicated that Nigella sativa could be a beneficial supplement for lung cancer patients.